APLIKASI PPH FINAL USAHA JASA KONSTRUKSI PADA PT. WIKA REALTY PROYEK PERUMAHAN GRAND TAMANSARI - Imam Nazarudin Latif, Normansyah Elfreda Aplonia Lau (EKONOMIA, 2015)
The purpose of this study was to determine and analyze the amount of final income tax rates and taxes on construction services are implemented by PT . Wijaya Karya Realty in Grand Castle Samarinda housing project in 2013. The analysis tool used is the calculation of the final income tax on construction services under Government Regulation No. 40 in 2009 and compare it with the calculation of the company . Based on the results of research conducted found differences in applying the final income tax on construction services that are individual . PT . Wika Realty for housing project Grand Castle PPH 21 Samarinda apply if the contractor who is peorangan do the job on the basis of SP3 ( Job Execution Warrant ) and apply the final income tax when executing construction work on the basis of the SPK ( Work Order )